Time‐Domain Analysis of Heart Sound Intensity in Children with and without Pulmonary Artery Hypertension: A Pilot Study using a Digital Stethoscope. (1st December 2014) - Elgendi, Mohamed; Bobhate, Prashant; Jain, Shreepal; Rutledge, Jennifer; Coe, James Y.; Zemp, Roger; Schuurmans, Dale; Adatia, Ian
Abstract : We studied digital stethoscope recordings in children undergoing simultaneous catheterization of the pulmonary artery (PA) to determine whether time‐domain analysis of heart sound intensity would aid in the diagnosis of PA hypertension (PAH). Heart sounds were recorded and stored in. wav mono audio format. We performed recordings for 20 seconds with sampling frequencies of 4, 000 Hz at the second left intercostal space and the cardiac apex. We used programs written in the MATLAB 2010b environment to analyze signals. We annotated events representing the first (S1) and second (S2) heart sounds and the aortic (A2) and pulmonary (P2) components of S2. We calculated the intensity ( I ) of the extracted event area ( x ) as I k = ∑ i = 1 n ( x k ( i ) ) 2, where n is the total number of heart sound samples in the extracted event and k is A2, P2, S1, or S2. We defined PAH as mean PA pressure (mPAp) of at least 25 mmHg with PA wedge pressure of less than 15 mmHg. We studied 22 subjects (median age: 6 years [range: 0.25–19 years], 13 female), 11 with PAH (median mPAp: 55 mmHg [range: 25–97 mmHg]) and 11 without PAH (median mPAp: 15 mmHg [range: 8–24 mmHg]). The P2 ? A2 ( P =. 0001) and P2 ? S2 ( P =. 0001) intensity ratios were significantly different between subjects with and those without PAH. There was a linear correlation ( r > 0.7) between the P2 ? S2 and P2 ? A2 intensity ratios and mPAp. We found that the P2 ? A2 and P2 ? S2 intensity ratios discriminated between children with and those without PAH. These findings may be useful for developing an acoustic device to diagnose PAH.